The wicked problem of teaching about wicked problems: Design thinking and emerging technologies in sustainability education. Issue 5 (November 2021) - Earle, Andrew G.; Leyva-de la Hiz, Dante I.
In this paper, we explore the system-level challenges found in sustainability-focused education and consider how the intersections of design thinking and emerging technologies in augmented and virtual reality (AVR) can help address these. More specifically, we highlight the role of experiences across the design thinking process for generating novel solutions to the types of "wicked" problems with which students engage in sustainability education. We then use this as motivation, along with concepts from experiential learning and design thinking research, to develop a conceptual model in which AVR can integrate with more established instructional methods to help make sustainability-related challenges more salient, proximate, and tractable to students. Our conceptual model suggests that AVR holds promise for facilitating and democratizing access to the design thinking process for sustainability-related challenges, but that it is also not a standalone solution for enabling students to engage with such complex challenges.